Peningkatan Pemahaman Pelajaran Ilmu Pengetahuan Alam Pokok Bahasan Energi dan Perubahannya Melalui Strategi Pembelajaran Active Learning Group Resume pada Peserta Didik Kelas VI SDN Lembursitu 2 Sukabumi - Sindawati, Etty (FKIP Universitas Muhammadiyah Sukabumi, 2018)
The subject of natural science which is hard to undesrtand by students from grade VI SDN Lembursitu2 Sukabumi is the concept of Energy and Its Change. This is proven by a gaps between the score of practise islower than the score of concept. Therefore the classroom action research is conducted to know the efectivityabout learning strategy of Active Learning Group Resume in improving student’s understanding the concept ofEnergy and Its Change. Research sampling included with 34 students grade VI SDN Lembursitu 2 Sukabumi.Research method is used by descriptive study, and data collecting technique consist of observation, interview,study of document, and test, and data analyze is done by quantitative-descriptive. The result shows that there isan increased in learning outcomes of student through learning strategy of Active Learning Group Resume. Thisis proven by the student average score is from 56,61 to 65,14 in 1st cycle and 73,23 in 2nd cycle. This classroomaction research is considered as successful because of the student average score reached 73,23 %, which meanexceed KKM’s score is 70.